Poor outcomes associated with +der(22)t(9;22) and −9/9p in patients with Philadelphia chromosome‐positive acute lymphoblastic leukemia receiving chemotherapy plus a tyrosine kinase inhibitor. Issue 3 (3rd February 2017) - Short, Nicholas J.; Kantarjian, Hagop M.; Sasaki, Koji; Ravandi, Farhad; Ko, Heidi; Cameron Yin, C.; Garcia‐Manero, Guillermo; Cortes, Jorge E.; Garris, Rebecca; O'Brien, Susan M.; Patel, Keyur; Khouri, Maria; et al.
Abstract: In patients with Philadelphia chromosome‐positive (Ph+) acute lymphoblastic leukemia (ALL) treated with chemotherapy plus a tyrosine kinase inhibitor (TKI), the prognostic impact of additional chromosomal abnormalities (ACAs) is not well‐established. We evaluated the prognostic impact of individual ACAs in 152 patients with Ph+ ALL receiving first‐line intensive chemotherapy plus either imatinib ( n = 36), dasatinib ( n = 74), or ponatinib ( n = 42). ACAs were identified in 118 patients (78%). Compared to outcomes of patients without ACAs, ACAs were not associated with differences in either relapse‐free survival (RFS; P = 0.42) or overall survival (OS; P = 0.51). When individual ACAs were evaluated, +der(22)t(9;22) and/or −9/9p in the absence of high hyperdiploidy (HeH) was present in 16% of patients and constituted a poor‐risk ACA group. Patients with one or more poor‐risk ACAs in the absence of HeH had significantly shorter RFS (5‐year RFS rate 33% versus 59%, P = 0.01) and OS (5‐year OS rate 24% versus 63%, P = 0.003). Poor‐risk ACAs were prognostic in patients who received imatinib and dasatinib but not in those who received ponatinib. By multivariate analysis, this poor‐risk ACA group was independently associated with worse RFS (HR 2.03 [95% CI 1.08‐3.30], P = 0.03) and OS (HR 2.02 [95% CI 1.10‐3.71], P = 0.02). Patients with Ph+ ALL who have +der(22)t(9;22) and/or −9/9p in the absence of HeH have relatively poor outcomes when treated with chemotherapy plus a TKI.